Discourse Markers Analysis In The Ron Clark Story Movie - Akbar, Ridhoni; Mariani, Nanik; Elyani, Eka Puteri (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
This research investigates the discourse makers found in The Ron Clark Story movie. Discourse makers are words that link the speaker to what has been uttered previously. This can improve a speaker's ability to communicate clearly. This research analyzes the discourse makers found in every scene The Ron Clark Story movie. A qualitive descriptive method was used to analyze the collected data. The result of this study the discourse marker "and" is most often usedÂ  in The Ron Clark Story movie. It can be seen from the data that it was used 76 times out of a total of 211. Besides, the least discourse marker is "I mean" which is used 6 times.